Animated Three-Dimensional Payment of Motor Vehicle Taxes at Samsat Gerai Bencoolen Mall - Koko Saputra; Agung Kharisma Hidayah (Jurnal Komputer, Informasi dan Teknologi, 2022)
With the development of the times, currently animation is not only used for entertainment. However, animation can be used as a tool to help humans in everyday life. Animation has the ability to explain something that is not understood only through pictures and sentences. By means of visualization, an intention can be described. In the motor vehicle tax payment process, animation can also help the community, for example, the procedures for paying motor vehicle taxes at the Samsat Bencoolen Mall outlet. So to make it easier for the public to get information on how to pay motorized vehicle taxes at the Samsat Bencoolen Mall outlet, it is necessary to have a media for delivering information that is more efficient, can be understood easily by the public and is more attractive. Therefore, in this study an animated video will be made of the procedures for paying taxes at a multimedia-based, multimedia-based samsat bencoolen mall outlet in the form of three-dimensional animation as a means of information that is shown for people who want to pay taxes and to the wider community. As will be discussed at this time, namely "Payment of Motor Vehicle Taxes at Samsat Bencoolen Mall Stores" using Blender Software. In connection with this research carried out during the Covid-19 pandemic, the author will accompany the video flow of motor vehicle tax payments at the Samsat Bencoolen Mall outlet independently or commonly called Self Service.